Multi-criteria linear-quadratic control problem by KSH-direction interior-point method - Kanuengkid W. (2014)
We describe an implementation of an infinite dimension interior-point method for solving multi-criteria linear -quadratic control problem based on KSH-direction. It is shown that such a descent direction is independent on the scaling point. Each iteration requires solving finite rank perturbation of linear-quadratic control problems and a system of algebraic equations. The numerical result shows rapid convergence to the optimal solution.